The BDNF Val66Met Polymorphism Modulates Resilience of Neurological Functioning to Brain Ageing and Dementia: A Narrative Review - Brown, Donnamay T; Vickers, James C; Stuart, Kimberley E; Cechova, Katerina; Ward, David D (Brain sciences, 2020)
Brain-derived neurotropic factor (BDNF) is an abundant and multi-function neurotrophin in the brain. It is released following neuronal activity and is believed to be particularly important in strengthening neural networks. A common variation in the BDNF gene, a valine to methionine substitution at codon 66 (Val66Met), has been linked to differential expression of BDNF associated with experience-dependent plasticity. The Met allele has been associated with reduced production of BDNF following neuronal stimulation, which suggests a potential role of this variation with respect to how the nervous system may respond to challenges, such as brain ageing and related neurodegenerative conditions (e.g., dementia and Alzheimer's disease). The current review examines the potential of the BDNF Val66Met variation to modulate an individual's susceptibility and trajectory through cognitive changes associated with ageing and dementia. On balance, research to date indicates that the BDNF Met allele at this codon is potentially associated with a detrimental influence on the level of cognitive functioning in older adults and may also impart increased risk of progression to dementia. Furthermore, recent studies also show that this genetic variation may modulate an individual's response to interventions targeted at building cognitive resilience to conditions that cause dementia.
Keywords: ageing; dementia; brain-derived neurotrophic factor; BDNF Val66Met; cognitive function; Alzheimer’s disease; BDNF